(untitled) (European Journal of Formal Sciences and Engineering, 2021)
Solitons are structurally stable solitary waves that propagate in a nonlinear medium. In this paper, solitons will be considered as the basis for solving many classical nonlinear equations of motion. Some classical solutions that were modeled through the application of Wolfram Mathematica System and MATLAB programming language. In this paper some soliton solutions will also be compared and some types of solitons were modeled.The dynamics of solitons was studied in consideration of solutions of some equations, such as the Korteweg - de Vries equation and as a particular solution for the nonlinear Schrödinger equation provided that the nonlinearity parameter R-0 in the equation. We concluded by showing solitons in more detail which are often used in practice as a simpler method for explaining complex phenomena and solving non-classical equations